Science Development Trends with the Metaphor of the Tree of Science State Islamic University of Maulana Malik Ibrahim Malang - Khoiriyah, Siti; Fuad, Ah Zakki; Bakar, M Yunus Abu (Al Hikmah: Journal of Education, 2023)
This study aims to identify and analyze trends in science development using the metaphor of "Tree of Science" within Maulana Malik Ibrahim State Islamic University Malang (UIN Malang). This metaphor is used as a conceptual framework to understand the development of various disciplines at the university. This research uses content analysis methods against official documents, such as university development plans, curricula, and scientific publications related to academic programs. The results showed that UIN Malang has adopted and developed the metaphor of "Tree of Science" as a strategic foundation in the development of science. There are three trends in the development of science at UIN Malang including: 1) using the integrative curriculum model of ma'had al-Jami'ah. 2) through the Arabic and English Language Development Program. 3) Through character education based on ulul albab.